ANALISIS KINERJA KEUANGAN PT MITRA PINASTHIKA MUSTIKA TBK DAN ENTITAS ANAK DENGAN ANALISIS RASIO DAN DU PONT SYSTEM - Rutmana, Puspa; Medinal; Ahmad Agin, Arka'a (Jurnal Akuntansi Bisnis Dan Keuangan, 2019)
This research was written by Puspa Rutmana, NIM 130150084 with the title "Financial Performance Analysis of PT Mitra Pinasthika Mustika Tbk and Subsidiaries with Analysis of Ratio and Du Pont System". The purpose of this study was to determine and analyze the financial performance of PT. Mitra Pinasthika Mustika Tbk and Subsidiaries by applying ratio analysis and du pont system. The analytical method used is the descriptive analysis method in times series and trend analysis. The results showed that the financial performance of PT. Pinasthika Mustika Tbk and Subsidiaries with the application of ratio analysis consisting of liquidity ratios, leverage, activity, and profitability are good enough but the analysis of the du pomt system is less good compared to the average of similar industries. The conclusion that can be drawn from this study is that the Pinasthika Mustika Tbk Partners and Entities must continue to continuously pay attention and improve financial performance based on financial performance measured through ratio analysis especially if further analysis is done through the du pont system. For other researchers who want to find out more about the factors that affect financial performance can add or expand the independent variables in further research.